The sculpture of Ganesha - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum) of the temple houses a sculpture of Ganesha. He is shown dancing gracefully. Although he originally had multiple arms, only the upper two remain intact, holding a snake. A halo in the form of a full-blown flower surrounds his form.